Essential Oils - Oils of Nature 2020
DOI: 10.5772/intechopen.85638
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Microbial Communication

Abstract: The World Health Organization highlighted the increase in the resistance to conventional antibiotics for most pathogens and observed also a decrease of the threshold for all mechanisms of cell-cell microbial communication, leading to the formation of biofilms and to the increase of microbial pathogenicity. Scientific community is therefore oriented to the identification and study of alternative substances to antibiotics. In such context, substances of vegetal source, such as essential oils (EOs), always used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 113 publications
2
15
0
1
Order By: Relevance
“…Indeed, this compound alters cell membrane, inhibits respiratory chain and attenuates genes expression involved in bacterial resistance 32 in several positive and negative strains 53,54 . Moreover, carvacrol can also inhibit the bacterial communication by interfering quorum sensing signalling pathways, which are involved on the establishment of biofilm formation and bacterial resistance to antibiotics 55 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this compound alters cell membrane, inhibits respiratory chain and attenuates genes expression involved in bacterial resistance 32 in several positive and negative strains 53,54 . Moreover, carvacrol can also inhibit the bacterial communication by interfering quorum sensing signalling pathways, which are involved on the establishment of biofilm formation and bacterial resistance to antibiotics 55 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been demonstrated that a stress induced by thymol influences the S. typhimurium proteome, downregulating genes involved in chemotaxis, motility, and virulence [20]. In addition, it is reported that these substances can affect quorum sensing of bacteria [40], which, in turn, controls virulence factor production [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Nazzaro et al . (2019) added that terpenoids (carvacrol, linalyl acetate, linalool, thymol, geraniol, piperitone and menthol citronellal) have antibacterial effects due to the presence of functional group on the bacterium outer membrane, leading to changing the membrane fluidity and/or permeability and altering their periplasmic enzymes and protein content. This came on line with Helander et al .…”
Section: Antibacterial Effectmentioning
confidence: 99%